All Saints Episcopal Church, (Franklin St.), Richmond, Va. (16836445441) - VCU Libraries Commons (Wikimedia Commons, 2015)
Carte postale ancienne issue de Wikimedia Commons. Titre: All Saints Episcopal Church, (Franklin St.), Richmond, Va. (16836445441). Description: This handsome French Gothic building was completed in Jan. 1901, and takes the place of a much more modest house of worship, which the progressive congregation found too small for its purposes. The present building has a seating capacity of about 1000, and contains a number of beautiful memorial windows | those in the chancel, illustrating the Te Deum, being especially worthy of mention. Manufacturer: Southern Bargain House, Richmond, Va. Date Postmarked: Not postmarked. Rights: This item is in the public domain. Acknowledgement of the Virginia Commonwealth University Libraries as a source is requested. Reference URL: dig.library.vcu.edu/u?/postcard,562 Collection: Rarely Seen Richmond: Early twentieth century Richmond as seen through vintage postcards
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale